The Effect of Convenience Benefits, Consumer Knowledge, And Promotion on Interest in Using E-Money (Studies in the City of Bengkalis) - Deby Rahmadona; Yunelly Asra (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
This research aims to analyze the benefits, consumer knowledge, and promotion of interest using e-money in Bengkali city. Type of research is quantitative associative research which aims to see: The effect of benefits on the interest using e-money, the effect of consumer knowledge on use of e-money, the effect of promotion on interest using e-money, the influence of dominant influence from the effect of appropriate benefits, consumer knowledge, and promotion on interest using e-money. The population this study of Bengkalis city. Sampling selected based on population elements whose data easily obtained by researchers. Data analysis used was multiple regression analysis and hypothesis testing the T test and F test. The researcher suggests the providers and their supporting factors for e-money; increase the number of merchants to serve e-money users, increase number of advertisements to increase the e-money users, cooperate with SMEs order to become new trend of transaction tools.